Application of mid-infrared spectroscopy for soil analysis in calcareous Argania spinosa forests in Morocco - Lars Engelmann; Reinhard Bierl; Mario Kirchhoff; Johannes B. Ries (Geoderma Regional, 2025)

P24-01 Impact of perinatal and subchronic dietary glyphosate exposure on gut microbiota and liver metabolism in mice - C.M.P. Martin; L. Smith; L. Evariste; F. Lasserre; A. Polizzi; V. Alquier-Bacquie; C. Dauriat; B. Engelmann; U. Rolle-Kampczyk; M. Von Bergen; B. Lamas; E. Houdeau; et al. (Toxicology Letters, 2024)

P09-12: Exploring the regulatory effects of lysine acetylation and phosphorylation in adipocyte differentiation and their exposure to emerging plastic additives - A.S. Aldehoff; I. Karkossa; B. Engelmann; U. Rolle-Kampczyk; M. von Bergen; K. Schubert (Toxicology Letters, 2023)

Pro- and anti-inflammatory macrophages express a sub-type specific purinergic receptor profile - J. Merz; A. Nettesheim; S. von Garlen; P. Albrecht; B. S. Saller; J. Engelmann; L. Hertle; I. Schäfer; D. Dimanski; S. König; L. Karnbrock; K. Bulatova; et al. (Purinergic Signalling, 2021)
Extracellular nucleotides act as danger signals that orchestrate inflammation by purinergic receptor activation. The expression pattern of different purinergic receptors may correlate with a pro- or anti-inflammatory phenotype. Macrophages function as pro-inflammatory M1 macrophages (M1) or anti-inflammatory M2 macrophages (M2). The present study found that murine bone marrow-derived macrophages express a unique purinergic receptor profile during in vitro polarization. As assessed by real-time polymerase chain reaction (PCR), Gαs-coupled P1 receptors A2A and A2B are upregulated in M1 and M2 compared to M0, but A2A 15 times higher in M1. The ionotropic P2 receptor P2X 5 is selectively upregulated in M1- and M2-polarized macrophages. P2X 7 is temporarily expressed in M1 macrophages. Metabotropic P2Y receptors showed a distinct expression profile in M1 and M2-polarized macrophages: Gαq coupled P2Y 1 and P2Y 6 are exclusively upregulated in M2, whereas Gαi P2Y 13 and P2Y 14 are overexpressed in M1. This consequently leads to functional differences between M1 and M2 in response to adenosine di-phosphate stimulation (ADP): In contrast to M1, M2 showed increased cytoplasmatic calcium after ADP stimulation. In the present study we show that bone marrow-derived macrophages express a unique repertoire of purinergic receptors. We show for the first time that the repertoire of purinergic receptors is highly flexible and quickly adapts upon pro- and anti-inflammatory macrophage differentiation with functional consequences to nucleotide stimulation.

Application of immobilized synthetic anti-lipopolysaccharide peptides for the isolation and detection of bacteria - N. Sandetskaya; B. Engelmann; K. Brandenburg; D. Kuhlmeier (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Chronic wheel running reduces maladaptive patterns of methamphetamine intake: regulation by attenuation of methamphetamine-induced neuronal nitric oxide synthase - Alexander J. Engelmann; Mark B. Aparicio; Airee Kim; Jeffery C. Sobieraj; Clara J. Yuan; Yanabel Grant; Chitra D. Mandyam (Brain Structure and Function, 2014)

Brain responses to erotic and other emotional stimuli in breast cancer survivors with and without distress about low sexual desire: a preliminary fMRI study - Francesco Versace; Jeffrey M. Engelmann; Edward F. Jackson; Aurelija Slapin; Kristin M. Cortese; Therese B. Bevers; Leslie R. Schover (Brain Imaging and Behavior, 2013)

A simple protocol for cryopreservation of zygotic embryos of ten accessions of coconut (Cocos nucifera L.) - O. N’Nan; M. Borges; J.-L. Konan Konan; V. Hocher; J.-L. Verdeil; J. Tregear; A. S. P. N’guetta; F. Engelmann; B. Malaurie (In Vitro Cellular & Developmental Biology - Plant, 2012)

In vitro production of radiolabeled red clover (Trifolium pratense) isoflavones - Nancy J. Engelmann; Adam Reppert; Gad Yousef; Randy B. Rogers; Mary Ann Lila (Plant Cell, Tissue and Organ Culture (PCTOC), 2009)